Membrane interaction to intercellular spread of pathology in Alzheimer’s disease - Valappil, Deepak Kunhi; Mini, Neeraj Jayakumar; Dilna, Aysha; Nath, Sangeeta (Frontiers in Neuroscience, 2022)
Abstract Progressive development of pathology is one of the major characteristic features of neurodegenerative diseases. Alzheimer disease (AD) is the most prevalent among them. Extracellular amyloid-β (Aβ) plaques and intracellular tau neurofibrillary tangles are the pathological phenotypes of AD. However, cellular and animal studies implicate tau as a secondary pathology in developing AD while Aβ aggregates is considered as the disease drive a trigger point. Interaction of Aβ peptides with plasma membrane (PM) seems to be a promising site of involvement in the events that lead to AD. Aβ binding to the lipid membranes initiates formation of oligomers of Aβ species, and these oligomers are known as primary toxic agents for neuronal toxicities. Once initiated, neuropathological toxicities spread in a ‘prion-like’ fashion probably through the mechanism of intercellular transfer of pathogenic aggregates. In the last two decades, several studies have demonstrated neuron-to-neuron transfer of neurodegenerative proteins including Aβ and tau via exosomes and tunneling nanotubes (TNTs), the two modes of long-range intercellular transfer. Emerging pieces of evidence indicate that molecular pathways related to the biogenesis of exosomes and TNTs interface with endo-lysosomal pathways and cellular signaling in connection to vesicle recycling-imposed PM and actin remodulation. In this review, we discuss interactions of Aβ aggregates at the membrane level and its implications in intercellular spread of pathogenic aggregates. Furthermore, we hypothesize how spread of pathogenic aggregates contributes to complex molecular events that could regulate pathological and synaptic changes related to AD.